If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f-8=1/2-8+3
We move all terms to the left:
f-8-(1/2-8+3)=0
We add all the numbers together, and all the variables
f-8-(1/2-5)=0
We get rid of parentheses
f-8+5-1/2=0
We multiply all the terms by the denominator
f*2-1-8*2+5*2=0
We add all the numbers together, and all the variables
f*2-7=0
Wy multiply elements
2f-7=0
We move all terms containing f to the left, all other terms to the right
2f=7
f=7/2
f=3+1/2
| 2n+7=3n-47 | | p+2.9=9.9 | | 5w=4w-9 | | 1n+7=180 | | 39=m-122 | | 25/11=50/x | | 2((x-7)^5)+3=67 | | -7x+4x+8=2(x-6) | | r/19=-29 | | 9x+4=-40 | | 2.475=a/4 | | z+200=961 | | 180=3n-47 | | -28w=224 | | C=37.77+0.25x | | –7m+13=–64 | | 20/5y=40 | | x2–12x=45 | | 1+|5x-1|=3x-8 | | –3s−20=20−7s+20 | | y/9=22 | | n-20=37/9 | | 2f-3(15-f)=5 | | -11=5n+6n+24 | | D=2d-9 | | 1+|5x-1|=3x-1-8 | | -3h=-21 | | -35=11n | | –6+2s=4s+10 | | ½=6x | | 4y-24.3=27.7 | | 98=d+46 |